HAPPINESS AND MEANING IN IMPRISONMENT: THE IMPORTANCE OF SUFFERING IN THE EXPERIENCES OF NICOLAE STEINHARDT AND VIKTOR FRANKL - STADOLEANU, Carmen (Studia Universitatis Babeș-Bolyai Philosophia, 2022)
The paper describes the experiences of Nicolae Steinhardt and Viktor Frankl, both imprisoned despite their innocence, and their discovery of happiness and meaning through suffering and pain. Nicolae Steinhardt was a Romanian political prisoner of the communist regime and Viktor Frankl was a Jew imprisoned in the Auschwitz concentration camp. While in prison, Nicolae Steinhardt is secretly baptized and his life takes a very interesting turn. The discovery of God gives him access to the phenomenon of happiness and as he confesses, in prison he will live the happiest days of his life. Despite the miserable conditions, the pain, and the physical and mental torment, Steinhardt characterizes his happiness as ecstatic, passionate and life-changing. Under similar conditions, Viktor Frankl discovers the importance of suffering in determining the meaning of life. For Frankl, life always holds a potential meaning and if there is a meaning in life at all, then there must be a meaning in suffering. Therefore, through suffering and sorrow, and not in spite of them, Steinhardt and Frankl gain access to happiness and meaning.